P-015 Implementation of a cognitive dysfunction screening protocol after aneurysmal subarachnoid hemorrhage. (23rd July 2022) - Hall, N; Jackson, J; Chitale, R; Fusco, M; Considine, C; Froehler, M
Abstract : Background: Implementation of a standardized cognitive assessment strategy after aneurysmal subarachnoid hemorrhage (aSAH) has not been reported in the literature, despite frequency of post-aSAH cognitive impairment and recommendations to perform cognitive assessment on all stroke patients. The aim of this study is to implement an evidence-based protocol for cognitive dysfunction screening and management after aSAH. Methods: A cognitive dysfunction screening protocol was developed, which included the Montreal Cognitive Assessment (MoCA) tool. Patients with identified cognitive dysfunction defined as MoCA score <26 were referred to neurocognitive rehabilitation and those with MoCA score 26–29 were referred for neuropsychological evaluation. The modified Rankin scale (mRS) was also used to assess functional status. Following a peer-led education session with nurses and physicians, the protocol was implemented over a six-month period in the Cerebrovascular Clinic associated with a large academic medical center. Results: A total of 20 patients were seen for post-hospital follow-up after aSAH between February 1 and July 31, 2021. Patients were included if the appointment was in-person, they spoke English, and were able to follow commands. Of the 16 patients included, 93.8% (15) underwent cognitive screening, with mean MoCA score 21 and mean mRS score 1.6. Clinician compliance with the protocol for cognitive dysfunction screening and management was observed in 93.8% of eligible patient encounters. In the 86.7% (13) of study patients who had cognitive impairment (MoCA <26), the mean mRS was 1.8. For patients (2) without cognitive impairment, the mean mRS was 1.0. There was no statistically significant difference in mRS between those with and without cognitive dysfunction. Conclusion: We successfully implemented an evidence-based screening protocol for cognitive dysfunction after aSAH. Most of these patients did exhibit cognitive dysfunction using the MoCA despite a good functional recovery, defined as mRS score < 2. Screening only with the mRS is inadequate to identify the substantial cognitive dysfunction within this patient population. Further research is necessary to understand the impact of early cognitive intervention on long term outcomes for patients with cognitive impairment following aSAH. Disclosures: N. Hall: None. J. Jackson: None. R. Chitale: None. M. Fusco: None. C. Considine: None. M. Froehler: None.